2007
DOI: 10.1515/znb-2007-0203
|View full text |Cite
|
Sign up to set email alerts
|

Neue Arsenide mit ThCr2Si2- oder einer damit verwandten Struktur: Die Verbindungen ARh2As2 (A: Eu, Sr, Ba) und BaZn2As2 / New Arsenides with ThCr2Si2-type or Related Structures: The Compounds ARh2As2 (A: Eu, Sr, Ba) and BaZn2As2

Abstract: Four new arsenides of rhodium and zinc were prepared by heating mixtures of the elements at high temperatures (1000 -1200 • C) and investigated by single crystal X-ray methods. EuRh 2 As 2 (a = 4.067(1), c = 11.319(2)Å) and BaRh 2 As 2 (a = 4.053(1), c = 12.770(3)Å) crystallize with the well-known ThCr 2 Si 2 -type (I4/mmm; Z = 2). Due to the rigid layers of RhAs 4 tetrahedra, and to the atomic size of europium and barium, the As-As distances between the layers with values of 2.97 and 3.66Å, respectively, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 6 publications
2
21
0
1
Order By: Relevance
“…Layered ternary compounds, AB 2 X 2 (A = rare earth or alkaline earth metal; B = main group, metalloid; X = main group 14-17 element) or 1-2-2 phases, favor the ThCr 2 Si 2 (I4/mmm) structure type, with the CaAl 2 Si 2 structure type (P3m1) as a distant second (Grytsiv et al, 2002;Hellmann et al, 2007). There are a few other less commonly observed structure types for layered main group metalloids, such as -BaCu 2 S 2 (Pnma; Leoni et al, 2003) observed for BaAl 2 Si 2 (Condron et al, 2007), and EuIn 2 P 2 (Jiang & Kauzlarich, 2006).…”
Section: Commentmentioning
confidence: 99%
“…Layered ternary compounds, AB 2 X 2 (A = rare earth or alkaline earth metal; B = main group, metalloid; X = main group 14-17 element) or 1-2-2 phases, favor the ThCr 2 Si 2 (I4/mmm) structure type, with the CaAl 2 Si 2 structure type (P3m1) as a distant second (Grytsiv et al, 2002;Hellmann et al, 2007). There are a few other less commonly observed structure types for layered main group metalloids, such as -BaCu 2 S 2 (Pnma; Leoni et al, 2003) observed for BaAl 2 Si 2 (Condron et al, 2007), and EuIn 2 P 2 (Jiang & Kauzlarich, 2006).…”
Section: Commentmentioning
confidence: 99%
“…Moreover, very recently a new "122" iron-free pnictides, namely, SrNi 2 As 2 , [22] were synthesized. These materials, where magnetic metal (Fe) is completely replaced by the other 3d magnetic metal (Ni) or non-magnetic metals (Ru, Rh) arsenic is completely replaced by other pnictogen -phosphorus, belong to the above mentioned "122" family and are low-temperature SC's (T C ~ 0.3-3.0K), see [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[19] A generally accepted key aspect for both LaFeAsO and BaFe 2 As 2 families is a magnetic and structural phase transition in the undoped phases, occurring at temperatures between 140-203 K. [10,[20][21][22] In the course of this transition, the tetragonal symmetry of the ThCr 2 Si 2 -type structure (space group I4/mmm) turns into the orthorhombic b-SrRh 2 As 2 -type [23] (space group Fmmm) before antiferromagnetic spin-ordering emerges. Recently, we have elucidated the spin structure of BaFe 2 As 2 by single-crystal neutron diffraction.…”
mentioning
confidence: 99%